Alice’s anima: the obligation of a transmedia reading - Bonacho, Fernanda (2018)
Artigo baseado na comunicação proferida no "Barcelona International Seminar: Transmedia Literacy. From Storytelling to Interactivity in the era of Distributed Authorship", IN3-Digital Culture Research Program, realizado na Universitat Oberta de Catalunha, em Barcelona, 10 Dezembro 2013